Growing Independence: Making Practice Collaborative, Flexible, and Meaningful - Sam Nelson (Middle Grades Review, 2016)
The concept of practice, from a middle school student’s perspective, is mundane, redundant, perhaps yawn-inducing. This essay explains a first-hand account of an educator moving to a proficiency-based learning format and discovering how student proficiency does not often improve without engaging and flexible practice opportunities. Using middle level concepts and brain-based research, changes in the educator’s practice came to accommodate the needs of students and take away the stigma of practice as being boring or repetitive. The essay includes examples of learning targets, in-class activities, and curriculum structures.
Keywords: proficiency-based learning; proficiency-based assessment; middle school; middle level; early adolescence